Modern Diagnostic Methods and Algorithm for the Treatment of Vaginal Infections (Eurasian Medical Research Periodical, 2023)
In modern obstetric and gynecological practice, the problem of violation of the vaginal microflora is one of the most urgent because of the possibility of developing a whole complex of complications affecting the reproductive function of a woman. Mixed variants of vaginal infections have been little studied, however, it is necessary to distinguish them, since different forms of pathogen coexistence require an individual therapeutic approach